New methodology of fatigue life evaluation for multiaxially loaded notched components based on two uniaxial strain-controlled tests. (June 2018) - Branco, Ricardo; Prates, P.A.; Costa, J.D.; Berto, Filippo; Kotousov, Andrei
Highlights: New multiaxial fatigue life assessment model based on two uniaxial strain-controlled tests. Significant reduction of overall cost and effort associated with the evaluation of multiaxial fatigue life. Method based on strain energy density fatigue master curves defined as the sum of positive elastic and plastic components. Lifetime predictions nearly independent on the pairs of tests selected to generate the fatigue master curve. Very good correlation between experimental and predicted lives with all points within a factor of 2. Abstract: The present paper focuses on the application of the total strain energy density approach to assess fatigue life in notched samples subjected to multiaxial loading. This approach requires, as a starting point, a fatigue master curve defined in terms of total strain energy density versus number of cycles to failure, which is usually determined from a set of uniaxial fatigue tests using smooth standard specimens. In order to reduce the time and cost associated with the generation of the fatigue master curve, a straightforward methodology based on the outcomes of only two uniaxial strain-controlled tests is proposed. The methodology is applied to round bars with U-shaped notches subjected to proportional bending-torsion loading histories. A very good correlation between the experimental and the predicted life of the notched specimens is observed. In addition, the theoretical predictions are nearly independent of the pairs of uniaxial strain-controlled tests selected to obtain the fatigue master curve, which indicates a good robustness of the suggested methodology.